Investigating racial differences in clinical and pathological features of prostate cancer in South African men - Dewar, Malcolm James (Division of Urology, 2017)
The aim of this project is to study the clinical and pathological features of prostate cancer in men from different racial groups in the Western Cape in an attempt to define the characteristics of the disease locally. Specifically we wanted to compare black with coloured and white patients.